2007
DOI: 10.1128/jvi.02704-06
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Flavivirus NS5 Methyltransferase

Abstract: The plus-strand RNA genome of flavivirus contains a 5 terminal cap 1 structure (m 7 GpppAmG). The flaviviruses encode one methyltransferase, located at the N-terminal portion of the NS5 protein, to catalyze both guanine N-7 and ribose 2-OH methylations during viral cap formation. Representative flavivirus methyltransferases from dengue, yellow fever, and West Nile virus (WNV) sequentially generate GpppA 3 m 7 GpppA 3 m 7 GpppAm. The 2-O methylation can be uncoupled from the N-7 methylation, since m 7 GpppA-RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
492
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(531 citation statements)
references
References 45 publications
16
492
1
7
Order By: Relevance
“…This indicated that 5H1 bound to a linear amino acid sequence (continuous epitope). This epitope was mapped to a 13 aa stretch (residues 41-53) that forms a helix-turn motif in the crystal structure of the MTase domain (Zhou et al, 2007). This region of NS5 is of particular interest in the context of the predicted structure of the full-length NS5 protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that 5H1 bound to a linear amino acid sequence (continuous epitope). This epitope was mapped to a 13 aa stretch (residues 41-53) that forms a helix-turn motif in the crystal structure of the MTase domain (Zhou et al, 2007). This region of NS5 is of particular interest in the context of the predicted structure of the full-length NS5 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the structure of the full-length molecule is required to provide a more accurate model for functional analysis and drug design. While recent studies have elucidated separate crystal structures for the MTase and RdRp domains of WNV NS5 (Malet et al, 2007;Zhou et al, 2007), apparent instability of the full-length recombinant protein during purification precluded crystallization of the entire molecule. A possible solution to this dilemma is co-purification and co-crystallization of NS5 in the presence of a monoclonal antibody (mAb) that binds to both MTase and RdRp domains and stabilizes the full-length protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was highly sensitive to inhibition, as shown by the low IC 50 values of the co-product AdoHcy and the AdoMet analogue sinefungin. Interestingly, mutational analysis of NS5MTase WNV within the viral genome has shown that the 29O-MTase activity is important for WNV reproduction (Zhou et al, 2007). Our 29O-MTase assay will be useful for screening and characterizing potential inhibitors, as already demonstrated by the identification of two flavivirus MTase inhibitors (Luzhkov et al, 2007;Milani et al, 2009).…”
mentioning
confidence: 94%
“…By homology with other Flavivirus members, the catalytic region of the enzyme is located within the C-terminal portion of the NS5 protein. Additionally, the NS5 protein also contains methyltransferase activity in the N-terminal portion of the NS5 protein, which is involved in the capping of plus-strand genomic RNA (10)(11)(12). The overall architecture of the ZIKV RdRp most likely resembles the canonical right-hand conformation, consisting of fingers, palm, and thumb subdomains, that has been typical for all known polymerase structures and is similar to that reported for the RdRps of other members of the Flaviviridae family, including hepatitis C virus (HCV) and DFV.…”
mentioning
confidence: 99%